Silencing of GhKEA4 and GhKEA12 Revealed Their Potential Functions Under Salt and Potassium Stresses in Upland Cotton - Li, Yi; Feng, Zhen; Wei, Hengling; Cheng, Shuaishuai; Hao, Pengbo; Yu, Shuxun; Wang, Hantao (Frontiers in Plant Science, 2021)
The K+ efflux antiporter (KEA) mediates intracellular K+ and H+ homeostasis to improve salt tolerance in plants. However, knowledge of the KEA gene family in cotton is largely absent. In the present study, 8, 8, 15 and 16 putative KEA genes were identified in Gossypium arboreum, G. raimondii, G. hirsutum and G. barbadense, respectively. These KEA genes were classified into 3 subfamilies, and members from the same subfamilies showed similar motif compositions and gene structure characteristics. Some hormone response elements and stress response elements were found in the upstream 2000 bp sequence of GhKEAs. Transcriptome data showed that most of the GhKEAs were highly expressed in roots and stems. The qRT-PCR results showed that most of the GhKEAs responded to low potassium stress, salt stress and drought stress. VIGS experiments demonstrated that under salt stress, after silencing genes GhKEA4 and GhKEA12, the chlorophyll content, proline content, soluble sugar content, peroxidase (POD) activity and catalase (CAT) activity were significantly decreased, and the Na+/K+ ratio was extremely significantly increased in leaves, leading to greater salt sensitivity. Under high potassium stress, cotton plants silenced for the GhKEA4 could still maintain a more stable Na+ and K+ balance and the activity of transporting potassium ions from roots into leaves was reduced in cotton plants silenced for GhKEA12. Under low potassium stress, silencing the GhKEA4 increased the activity of plants to transport potassium to shoots under low potassium conditions, and silencing the GhKEA12 increased the ability of plants to absorb potassium, but accumulated more Na+ in leaves. These results provide a basis for further uncovering the biological roles of KEA genes in cotton development and adaptation to stress conditions.